CIHR Knowledge Translation Checklist - Girard, Marie-Eve (Université d'Ottawa | University of Ottawa, 2021)
This checklist was developed to help CIHR proposal writers think about all thesections in which knowledge translation can be addressed in a CIHR proposal. Use this checklist to check if you have included in your proposal all the important elements related to knowledge translation that are relevant to your research project in each section of the proposal (proposal summary, methodological approach, timeline,roles and responsibilities or description of partners, knowledge translation plan,budget and participant CV).
Keywords: Tool; Knowledge Mobilization; Knowledge translation; checklist